Bone Marrow Therapies for Chronic Heart Disease. (11th August 2015) - Behbahan, Iman Saramipoor; Keating, Armand; Gale, Robert Peter
Abstract: Chronic heart failure is a leading cause of death. The demand for new therapies and the potential regenerative capacity of bone marrow-derived cells has led to numerous clinical trials. We critically discuss current knowledge of the biology and clinical application of bone marrow cells. It appears unlikely that bone marrow cells can develop into functional cardiomyocyte after infusion but may have favorable paracrine effects. Most, but not all, clinical trials report a modest short- but not long-term benefit of infusing bone marrow-derived cells. Effect size appears to correlate with stringency of study-design: the most stringent trials report the smallest effect-sizes. We conclude there may be short- but not substantial long-term benefit of infusing bone marrow-derived cells into persons with chronic heart failure and any benefit observed is unlikely to result from trans-differentiation of bone marrow-derived cells into functioning cardiomyocytes. Stem Cells   2015;33:3212–3227